2019
DOI: 10.4143/crt.2018.314
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective Study of the Significant Predictive Role of Inflammatory Degree in Initial and Repeat Prostate Biopsy Specimens for Detecting Prostate Cancer

Abstract: Purpose The purpose of this study was to determine whether histologic inflammation (HI) in initial and repeat prostate biopsy specimens was significantly associated with the detection of prostate cancer. Materials and Methods Between 2005 and 2017, the clinicopathological records of patients with high prostatespecific antigen (PSA) levels who underwent initial and repeat prostate biopsies were retrospectively reviewed. The presence of HI and its degree in each biopsied … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…In case of clinical or imaging abnormalities, additional directed biopsies are performed [19]. The indications for a new biopsy are linked to the increase or persistence of a high PSA level, suspect digital rectal examination, and the presence of atypical small acinar proliferation on the first series, the existence of 'a diagnostic doubt on a first series of biopsies [20] The second series must include 4 to 6 additional biopsies, in the anterior apex and the transition zone (anterior fibromuscular stroma) in search of anterior cancer [21]. Many authors have shown in clinical studies that the percentage of cancers detected exclusively by additional transitional zone biopsies is very low [22] [23].…”
Section: Discussionmentioning
confidence: 99%
“…In case of clinical or imaging abnormalities, additional directed biopsies are performed [19]. The indications for a new biopsy are linked to the increase or persistence of a high PSA level, suspect digital rectal examination, and the presence of atypical small acinar proliferation on the first series, the existence of 'a diagnostic doubt on a first series of biopsies [20] The second series must include 4 to 6 additional biopsies, in the anterior apex and the transition zone (anterior fibromuscular stroma) in search of anterior cancer [21]. Many authors have shown in clinical studies that the percentage of cancers detected exclusively by additional transitional zone biopsies is very low [22] [23].…”
Section: Discussionmentioning
confidence: 99%
“…4,5 However, a growing body of evidence from men with benign biopsies followed for subsequent prostate cancer suggests that histologic inflammation may decrease prostate cancer risk. [6][7][8][9] Although several studies have investigated associations between multiple circulating inflammatory markers and prostate cancer risk, [10][11][12] no previous study has, to our knowledge, evaluated the association between pre-diagnostic histologic markers of inflammation in the prostate and subsequent risk of cancer.…”
Section: Introductionmentioning
confidence: 99%